Pengaruh Media Pembelajaran dan Motivasi terhadap Hasil Belajar Materi Asam dan Basa di SMAN 2 Tanjung Morawa - Gultom, Juan Andreas; Ajat Sudrajat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine whether there are differences in the learning outcomes of students who are taught with Phet Simulation Learning Media and Chat GPT as well as high and low learning motivation assisted by problem-based learning models on acid-base material, and see the interaction between learning media and student learning motivation. The population in this study was all grade XI students at SMAN 2 Tanjung Morawa. The sample was taken by purposive sampling of 2 classes with a total sample of 68 students. The hypothesis test was performed with a two-track ANNAVA. For phet simulation media and GPT chat, the price of Fcalculate 18.56 > Ftable 3.99 which means that Ha is accepted, it can be concluded that there is a difference in the average learning outcomes of students who are given phet simulation media with GPT chat on acid-base material. At high and low learning motivation Fcalculate 6,66 > Ftable 3,99 which means there is a significant difference in learning outcomes between high learning motivation and low learning motivation. Furthermore, the interaction between the learning media and learning motivation was found Fcalculate 19,13 > Ftable 3,99, which means that there was an interaction between the learning model and learning interest on learning outcomes.